Papuan Students’ Behavior amid Yogyakarta Community Environment - Annisa Fitrah Nurrizka; Drajat Tri Kartono; Ahmad Zuber (International Journal of Pedagogy and Teacher Education, 2018)
This research employed  a descriptive qualitative method, in which data and material needed was  obtained from interviews, observation, and based on f literature study on  journals, documents, electronic media and mass media  with descriptive analysis. This research aimsed It aims to analyze and to describe the behavior of Papuan students living in  community environment in Yogyakarta. From the result of  research on the students studied, it could be  found that some of students studied had  organizational behavior along  with surrounding  people  by participating in some society activities, such as gotong royong (mutual cooperation), rapat RT(neighborhood meeting), safeguarding environment, and etc. However, on the other hand in some areas of Yogyakarta , for example some people are not willing to accept their presence and giving  them dwelling  such as  boarding house, so that it indicates  discrimination against Papuan students. It is  due to  dysfunctional behavior, they have thereby disrupting integration and socialization process in society. Papuan students consider that their behavior is commons , but is s unacceptable to society.  They make noise by speaking loudly, drinking , and some act ions  resulting  in conflict with  surrounding people. Meanwhile,  they should create a relationship and structure with society in the environment where  they live.